Clinical Approach to Infection in the Compromised Host - Rubin, Robert H.; Young, Lowell S. (Springer US, 1995)
"Infection in the Compromised Host" has become a classic chapter in textbooks devoted to infectious diseases and internal medicine. The numbers of compromised hosts are increasing in the era of modem medicine because of our expanded capabilities to deal with difficult diseases, especially neoplasms. As a consequence, microbiologic complications related to the intensive care administered to these patients are increasing as well. Under these circum stances, not only does the underlying illness create conditions favorable for the development of unusual infections, but often the therapy contributes to the acquisition of potential pathogens that tum into agents responsible for severe and frequently fatal disease. Granulocytopenia and immunosuppression have been the two key factors in predisposing patients with cancer and other serious diseases to severe bacterial infections. Colonization by hospital-acquired pathogens and breaks in the anatomic barriers-as a result of disease or medical intervention-have contributed to the high incidence of infectious diseases in these patients. Although there is some overlap between the types of infection in granulocytopenic and immunosuppressed hosts, each of these clinical entities has distinctive features thatjustify considering them separately, reserving the term immunocompromised hosts only when refer ring to patients who are predisposed to opportunistic infections. For about two decades, infections in granulocytopenic patients have attracted the atten tion of clinicians because they represent a model for the study of antimicrobial drugs in hosts deprived of an essential element of defense against bacterial infection, that is, an adequate number of normally functioning granulocytes